2014
DOI: 10.1016/j.seizure.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral side-effects of levetiracetam in children with epilepsy: A systematic review

Abstract: Based on the findings in this systematic review, children using levetiracetam have a risk of developing several behavioral side-effects such as aggression, hostility and nervousness compared to children who do not use levetiracetam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 45 publications
4
49
1
3
Order By: Relevance
“…A further AE associated with LEV was nervousness/irritability, which has already been reported in a previous systematic review of open label studies aimed at assessing behavioural effects of LEV in children [16]. Psychiatric effects, such as anxiety, depression and psychosis, were very rarely M a n u s c r i p t associated with LEV in RCTs.…”
Section: A N U S C R I P Tmentioning
confidence: 69%
“…A further AE associated with LEV was nervousness/irritability, which has already been reported in a previous systematic review of open label studies aimed at assessing behavioural effects of LEV in children [16]. Psychiatric effects, such as anxiety, depression and psychosis, were very rarely M a n u s c r i p t associated with LEV in RCTs.…”
Section: A N U S C R I P Tmentioning
confidence: 69%
“…[25][26][27] Future research could examine whether the symptoms of CD we observed in prenatally LEV-exposed children have the same pharmacological mechanisms as those in individuals taking LEV for epilepsy. [25][26][27] Future research could examine whether the symptoms of CD we observed in prenatally LEV-exposed children have the same pharmacological mechanisms as those in individuals taking LEV for epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of LEV in people with epilepsy is associated with an increase in behavioral problems, including aggressive behavior. [25][26][27] Future research could examine whether the symptoms of CD we observed in prenatally LEV-exposed children have the same pharmacological mechanisms as those in individuals taking LEV for epilepsy. Alternatively, this could be related to exposure of the child to maternal behavioral problems at home.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, cognitive side effects (eg, fatigue, cognitive slowing) have been documented for older generation AEDs (eg, phenobarbital, valproic acid) and behavioral side effects (eg, irritability, aggression) for newer generation AEDs (eg, levetiracetam, gabapentin) . Levetiracetam is known to have an adverse behavioral side effect profile, with general behavioral problems (19%) and irritability (2.6%) noted in monotherapy, and irritability (4.7%), hyperexcitability (4.4%), and aggression (2.7%) noted in adjunctive use . To date, predictors of AED behavioral side effect tolerability in pediatric epilepsy is not well established .…”
Section: Introductionmentioning
confidence: 99%